Penelitian Tindakan Partisipatif Metode Par (Partisipatory Action Research) Tantangan dan Peluang dalam Pemberdayaan Komunitas - Siswadi, Siswadi; Syaifuddin, Ahmad (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2024)
The PAR method is often used in community service activities. In PAR method research, the community is not just the object of research, but also researchers who have the same authority and power as other researchers, and are also recipients of research benefits. The people involved gain knowledge about solving the problems they face, while researchers receive research results and reports. This community involvement is the main superiority value of PAR. However, the large role of the community is prone to giving rise to conflicts of interest which can affect the objectivity of PAR research itself. The method used in this research is literature study with qualitative analysis. The results of this research show that the PAR methodology offers several benefits such as a democratic and fair research process that can provide experience and knowledge to the communities involved. The basic idea of ​​PAR is to educate people to think critically about the life problems they face. PAR challenges include; The process of building a common vision and understanding of the roles between the community involved and researchers, maintaining the objectivity of information about the problem topic, contextual factors that occur during research, the time that can be very long and large resources as well as the measurement and relevance of research results. The solution is intensive socialization and FGDs with research stakeholders and consistency and focus of all parties must be maintained.